PENGARUH TERAPI MUROTTAL AL-QUR’AN UNTUK PENURUNAN NYERI PERSALINAN DAN KECEMASAN PADA IBU BERSALIN KALA I FASE AKTIF - Handayani, Rohmi; Fajarsari, Dyah; Trisna Asih, Dwi Retno; Rohmah, Dewi Naeni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Pain in the process of labor is physiological condition. But, if the pain was left, it can affect the mother’s condition in the form of fatigue, scared, worry and caused the stress that can increased the pain and affect the labor process. One of the pain redactor is murottal therapy. To know the influence of murottal al-qur’an therapy to primigravida labor pain intensity decrease in Prof. Dr. Margono Soekardjo Hospital Purwokerto in 2014. The type of research is pre experiment with pretest and posttest design. The sample in this study as many as 42 maternal. The sample taking technique used consecutive sampling method. The analysis used paired t test. The average of pain intensity before murottal therapy is 6,57, the average after murottal therapy is 4,93. Paired t test showed that there are differences pain intensity decrease before and after murottal therapy with p value<α (0,000<0,05).There are differences pain intensity decrease before and after murottal therapy. Midwives should be apply the murottal therapy to each maternal because it can reduce labor pain easily. Keywords : Labor, Pain, Anxiety, Murottal Therapy